Makna Penggunaan Frasa “Makanan dan Minuman, Hari Raya, Hari Sabat” Berdasarkan Kolose 2:16-17: Studi Eksegesis - Sarjono, Moses; Pane, Exson (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
The use of the phrase "food and drink, festivals, and Sabbath days" in the context of the Colossian congregation has been misinterpreted and become a central point of debate regarding the Mosaic Law. Through an analysis of this text in Colossians 2:16-17, it will help address the notion that the dietary laws of clean and unclean foods and the Sabbath were not abolished through Jesus' death on the cross. This exegetical study aims to explore the meaning of the original language, connecting it historically and textually to perspectives on the law under examination. The study results indicate that "food and drink" do not refer to clean and unclean foods, and "Sabbath" does not refer to the weekly Sabbath but rather to the annual Sabbaths, also known as special festival days in the Jewish calendar. This shows that Paul was not emphasizing the abolition of God’s moral law, but was addressing ritual practices that were merely shadows of things to come namely, Christ Himself.